Alcohol Elicits Functional and Structural Plasticity Selectively in Dopamine D1 Receptor-Expressing Neurons of the Dorsomedial Striatum - Wang, Jun (J Neurosci, 2015)
Addiction is thought to be a maladaptive form of learning and memory caused by drug-evoked aberrant synaptic plasticity. We previously showed that alcohol facilitates synaptic plasticity in the dorsomedial striatum (DMS), a brain region that drives goal-directed behaviors. The majority of DMS cells are medium spiny neurons (MSNs) that express dopamine D1 receptors (D1Rs) or D2 receptors (D2Rs), which drive “Go” or “No-Go” behaviors, respectively. Here, we report that alcohol induces cell type-specific synaptic and structural plasticity in the DMS. Using mice that express a fluorescence marker to visualize D1R or D2R MSNs, we show that repeated cycles of systemic administration of alcohol or alcohol consumption induces a long-lasting increase in AMPAR activity specifically in DMS D1R but not in D2R MSNs. Importantly, we report that alcohol consumption increases the complexity of dendritic branching and the density of mature mushroom-shaped spines selectively in DMS D1R MSNs. Finally, we found that blockade of D1R but not D2R activity in the DMS attenuates alcohol consumption. Together, these data suggest that alcohol intake produces profound functional and structural plasticity events in a subpopulation of neurons in the DMS that control reinforcement-related learning. SIGNIFICANCE STATEMENT Alcohol addiction is considered maladaptive learning and memory processes. Here we unraveled a long-lasting cellular mechanism that may contribute to the memory of alcohol-seeking behaviors. Specifically, we found that alcohol consumption produces a long-lasting enhancement of channel activity and persistent alterations of neuronal morphology in a part of the brain (DMS) that controls alcohol-drinking behaviors. Furthermore, we show that these alterations occur only in a subpopulation of neurons that positively control reward and reinforcement of drugs of abuse. Finally, we report that blocking the activity of this neuronal population reduces alcohol intake. As such synaptic and structural changes are the cellular hallmarks of learning and memory, and these neuroadaptations may drive the development of pathological heavy alcohol consumption.